Irrigation, drainage and salinity : (Hutchinson/FAO/UNESCO, 1973)
The topics considered in this book are: water and salt balances; soils in relation to salinity, irrigation and drainage; hydrophysics of arid and irrigated soils; chemistry of saline and alkali soils of arid zones; landscapes in relation to irrigation, drainage and salinity; quality of irrigation water; water, plant growth and crop irrigation requirements; plants in relation to waterlogging and salinity; irrigation systems and management; drainage systems and management; some effects of irrigation and drainage on soils; reclamation of saline and alkaline soils; design and operational recommendations for the establishment or improvement of irrigation and drainage projects